Rāmāyaṇa : "Bālabodhinī" ṭīkāsahita; āṭhoṃ khaṇḍa, pūrṇatayā saṃśodhita aura saṃskṛta - Tulasīdāsa ((Rājā) Rāmakumāra-Presa-Bukaḍipo uttarādhikārī Navalakiśora-Presa, 1956)
Hindu epic on the life and exploits of Rāma